Validation of the American College of Surgeons National Surgical Quality Improvement Program Risk Model for Patients Undergoing Panniculectomy. Issue 1 (July 2019) - Suresh, Visakha; Levites, Heather; Peskoe, Sarah; Hein, Rachel; Avashia, Yash; Erdmann, Detlev
Purpose: Panniculectomy procedures have been reported to significantly improve quality of life, increase mobility, and improve hygiene in patients with a significant pannus formation. The primary aims of this study were to determine which preoperative risk factors may be used to differentiate postoperative complication rate among patient cohorts and to validate utilization of the American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) risk calculator in patients undergoing panniculectomies. Methods: This retrospective study included all patients who underwent a panniculectomy procedure at our institution from 2005 to 2016. Baseline characteristics, preoperative risk factors, medical comorbidities, and postoperative complications were collected via retrospective chart review. Results: Two hundred sixty-four patients who underwent a panniculectomy were identified. The odds ratios of any postoperative complication were 8.26, 7.76, and 16.6 for patients with classes 1, 2, and 3 obesity, respectively ( P < 0.05). Statistical modeling was utilized to evaluate the predictive performance of the ACS-NSQIP Surgical Risk Calculator. We calculated the C-statistic for the ACS-NSQIP model to be only 0.61, indicating that although the model is associated with the risk of complication, it does not have a strong predictive value for this particular procedure. Discussion: This study is one of the first to characterize postoperative complication rate based on extremum of body mass index for panniculectomy patients. Our results show that the utilization of the ACS-NSQIP Risk Calculator in this particular patient population underestimates the complication risk as a whole, which may necessitate the future development of a separate risk assessment model for this procedure.